Inductive Power Transfer Subsystem for Integrated Motor Drive - Zbigniew Kaczmarczyk; Marcin Kasprzak; Adam Ruszczyk; Kacper Sowa; Piotr Zimoch; Krzysztof Przybyła; Kamil Kierepka (Energies, 2021)
An inductive power transfer subsystem for an integrated motor drive is presented in this paper. First, the concept of an integrated motor drive system is overviewed, and its main components are described. Next, the paper is focused on its inductive power transfer subsystem, which includes a magnetically coupled resonant circuit and two-stage energy conversion with an appropriate control method. Simplified complex domain analysis of the magnetically coupled resonant circuit is provided and the applied procedure for its component selection is explained. Furthermore, the prototype of the integrated motor drive system with its control is described. Finally, the prototype based on the gallium nitride field effect transistors (GaN FET) inductive power transfer subsystem is experimentally tested, confirming the feasibility of the concept.